FOXO4 interacts with p53 TAD and CRD and inhibits its binding to DNA - Mandal, Raju; Kohoutova, Klara; Petrvalska, Olivia; Horvath, Matej; Srb, Pavel; Veverka, Václav; Obsilova, Veronika; Obsil, Tomas (Protein science, 2022)
Transcription factor p53 protects cells against tumorigenesis when subjected to various cellular stresses. Under these conditions, p53 interacts with transcription factor Forkhead box O (FOXO) 4, thereby inducing cellular senescence by upregulating the transcription of senescence-associated protein p21. However, the structural details of this interaction remain unclear. Here, we characterize the interaction between p53 and FOXO4 by NMR, chemical cross-linking, and analytical ultracentrifugation. Our results reveal that the interaction between p53 TAD and the FOXO4 Forkhead domain is essential for the overall stability of the p53:FOXO4 complex. Furthermore, contacts involving the N-terminal segment of FOXO4, the C-terminal negative regulatory domain of p53 and the DNA-binding domains of both proteins stabilize the complex, whose formation blocks p53 binding to DNA but without affecting the DNA-binding properties of FOXO4. Therefore, our structural findings may help to understand the intertwined functions of p53 and FOXO4 in cellular homeostasis, longevity, and stress response.
Keywords: Tumor Suppressor Protein p53; vazba proteinů; DNA; Cell Cycle Proteins; Forkhead Transcription Factors; proteiny buněčného cyklu; Protein Binding; nádorový supresorový protein p53; forkhead transkripční faktory